Prevalence estimates of dementia in older adults in rural Kilimanjaro 2009–2010 and 2018–2019: is there evidence of changing prevalence?. (23rd February 2021) - Yoseph, Marcella; Paddick, Stella‐Maria; Gray, William K.; Andrea, Damas; Barber, Robyn; Colgan, Aoife; Dotchin, Catherine; Urasa, Sarah; Kisoli, Aloyce; Kissima, John; Haule, Irene; Rogathi, Jane; et al.
Abstract: Introduction: Although limited, existing epidemiological data on dementia in sub‐Saharan Africa indicate that prevalence may be increasing; contrasting with recent decreases observed in high‐income countries. We have previously reported the age‐adjusted prevalence of dementia in rural Tanzania in 2009–2010 as 6.4% (95% confidence interval [CI] 4.9–7.9) in individuals aged ≥70 years. We aimed to repeat a community‐based dementia prevalence study in the same setting to assess whether prevalence has changed. Methods: This was a two‐phase door‐to‐door community‐based cross‐sectional survey in Kilimanjaro, Tanzania. In Phase I, trained primary health workers screened all consenting individuals aged ≥60 years from 12 villages using previously validated, locally developed, tools (IDEA cognitive screen and IDEA‐Instrumental Activities of Daily Living questionnaire). Screening was conducted using a mobile digital application (app) on a hand‐held tablet. In Phase II, a stratified sample of those identified in Phase I were clinically assessed using the DSM‐5 criteria and diagnoses subsequently confirmed by consensus panel. Results: Of 3011 people who consented, 424 screened positive for probable dementia and 227 for possible dementia. During clinical assessment in Phase II, 105 individuals met DSM‐5 dementia criteria. The age‐adjusted prevalence of dementia was 4.6% (95% CI 2.9–6.4) in those aged ≥60 years and 8.9% (95% CI 6.1–11.8) in those aged ≥70 years. Prevalence rates increased significantly with age. Conclusions: The prevalence of dementia in this rural Tanzanian population appears to have increased since 2010, although not significantly. Dementia is likely to become a significant health burden in this population as demographic transition continues. Key Points: Using similar methodology, 9 years later, the prevalence of dementia appears to be increasing in Tanzania rather than decreasing, as observed in high‐income countries.